Beyond the dualism between domain-general and domain-specific abilities: a developmental approach to mathematical learning - Decarli, Gisella (Frontiers in Developmental Psychology, 2026)
Understanding how cognitive abilities support mathematical learning across development remains a central question in psychology. Traditionally, scietific literature has distinguished between domain-specific abilities, referring to processes specifically involved in quantity/numerical processing and supported by systems such as the Approximate Number System (ANS) and the Object Tracking System (OTS), and domain-general abilities, which encompass broader cognitive resources such as working memory and executive functions. This paper proposes a developmental and dynamic framework that integrates previous theoretical perspectives and extends them to the earliest stages of life, suggesting that early learning may rely primarily on mechanisms dedicated to numerical understanding, whereas with age and schooling, broader cognitive resources gradually become more influential in supporting complex mathematical reasoning.